Governance of Tax Institutions and Its Impact on Reducing Tax Evasion and Its Reflection on Tax Revenue: An Applied Study at the Iraqi General Tax Authority for the Period 2016–2025 - Arshed Rashed; Hayder Koshan; Ayyed Abbood (Penerbit Jurnal Indonesia, 2026)
The research aims Search to study effect Governance Institutions tax in Limit from Evasion tax and reflection that on more The outcome Taxation, from during study Applied on Authority public For taxes Iraqi For the period 2016–2025. Start Search from Two hypotheses Two main points : the first It benefits With the presence relationship Positive between quality Governance and limit from Evasion tax, The second It indicates to that to improve Governance Contributes in more Revenue Tax. Approved. Search on Curriculum Descriptive Analytical, Using Data Statistics For the result tax and reports The Authority addition to Surveys Interviews with employees And those obligated. And it was done analysis Data In style decline linear Relations Statistics Test The hypotheses showed Results that there impact positively and tangible For governance on Limit from Evasion tax, where Contributed elements Transparency and accountability and efficiency Organizational in to improve Performance tax For the Authority, And raised The outcome Annual For taxes. Also She showed the study that gaps in application Standards Governance Affect negatively on collection Revenue. Finished. Search to necessity Strengthening Organized censorship Interior, and application Technology Digital in procedures collection Taxes, and development Programs Training For employees Authority To promote Transparency And accountability, to side to improve legislation tax and increase Awareness between Those obligated. And they submitted This is amazing Results Contribution whatever in to understand relationship between Governance Institutions tax and effectiveness Revenue tax in Iraq.